Appendix S1. Ct values for qRT-PCR efficiency for Salmo salar. - Balasingham, Katherine D.; Walter, Ryan P.; Heath, Daniel D. (Dryad Digital Repository, 2016)
Ct values for Figure 2. 10-fold Salmo salar dilution series with Salmo_Mito-951 (d-loop; Karlsson et al. 2012) primer set.